2021
DOI: 10.1088/1361-6560/abd737
|View full text |Cite
|
Sign up to set email alerts
|

A commercial treatment planning system with a hybrid dose calculation algorithm for synchrotron radiotherapy trials

Abstract: Synchrotron Radiotherapy (SyncRT) is a preclinical radiation treatment which delivers synchrotron x-rays to cancer targets. SyncRT allows for novel treatments such as Microbeam Radiotherapy, which has been shown to have exceptional healthy tissue sparing capabilities while maintaining good tumour control. Veterinary trials in SyncRT are anticipated to take place in the near future at the Australian Synchrotron's Imaging and Medical Beamline (IMBL). However, before veterinary trials can commence, a computerised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The hybrid dose calculation algorithm was previously paired with the Eclipse TM treatment planning system (Varian Medical Systems, inc.), a commercially available graphical software routinely used for treatment planning in the clinic [47,48]. Eclipse TM was used to generate the phantom geometry and display the dose distribution, while the dose calculation was performed using the hybrid algorithm engine.…”
Section: Monte Carlo Simulations Of Depth Dose Profilementioning
confidence: 99%
“…The hybrid dose calculation algorithm was previously paired with the Eclipse TM treatment planning system (Varian Medical Systems, inc.), a commercially available graphical software routinely used for treatment planning in the clinic [47,48]. Eclipse TM was used to generate the phantom geometry and display the dose distribution, while the dose calculation was performed using the hybrid algorithm engine.…”
Section: Monte Carlo Simulations Of Depth Dose Profilementioning
confidence: 99%
“…There are some studies conducting the dose calculation accuracy of different TPS in more complex geometries. 14,27,59,24,23,[61][62][63] Bahreyni Toossi et al 27 quantified dose calculation accuracy of TiGRT TPS in a RANDO phantom. In that study, they planned two lateral parallel opposed fields on the head and neck region of the phantom, in which one of them was an open field and was wedged field.…”
Section: Evaluating the Dose Calculation Accuracy Of Isogray Tps Base...mentioning
confidence: 99%
“…Another challenge is the extreme high dose and dose rate that is required, although recent preclinical studies have shown that temporal fractionation of the dose delivery, into three sessions delivered over 3 days, may provide the same benefits [71]. Development of suitable treatment planning systems prior to studies in veterinary trials is also underway [72]. The recent interest in FLASH radiotherapy has led to renewed interest in the development of new compact accelerators that can deliver radiation at the high dose rates required for FLASH and potentially these could also be used to deliver MRT in the future in a more cost-effective manner [73,74].…”
Section: Future Developments and Clinical Utilitymentioning
confidence: 99%